FORMATION OF THE GROWING PERIOD INDICATOR IN COTTON OPTIONS (British Journal of Global Ecology and Sustainable Development, 2024)
In the article, despite the fact that convergent families based on the principle of transgressive recombination showed some lag compared to the standard variety C-6524 according to the results of the first year, as a result of correct selection in subsequent years, early maturity was achieved compared to the standard variety, while in long-term observations, convergent families based on the combined principle of transgressive recombination and incomplete backcrossing. It was noted that the family was superior to the S-6524 variety and showed more precocity.Among the convergent families founded on the principle of transgressive recombination, it was noted that the O-329-30 family, founded on the combined principle of transgressive recombination and incomplete backcrossing, was faster ripening O-521-22 than the other family and the standard variety.